Proposta de framework para intercooperação entre cooperativas agroalimentares atuando em rede horizontal - Mendina, Heitor José Cademartori (Universidade do Vale do Rio dos Sinos, 2015)
This thesis proposes a framework to encourage the inter-cooperation among agri-food cooperatives acting in a horizontal network. This framework was developed from the analytical model of research originated from the literature review, according to the methodology “Soft Systems Methodology”. This essay is a qualitative research based on study of multiple cases, performed in three networks in the southern region. This research has the assumption that inter-cooperation is a strategy for creating a competitive advantage in order to cooperatives be able to survive and grow in their own markets. The thesis found that there are factors which influence inter-cooperation and contribute in obtaining positive or negative results, depending on how they are managed. The impact generated by identified factors emerged from the collection of data from multiple sources of evidence: analysis of documentation, interviews with managers of networks and neutral observation of the researcher, from which triangulations were placed for analysis of the collected data. The results of the research showed that the driving factors of inter-cooperation were: presence of strong brand for the marketing of products, organizational learning, generation of economies of scale, reduction of costs, decision-making, use of formal mechanisms of governance, corporate co-participation, professionalized management, creation of independent business units, organizational culture of quality and sustainability, assistance to sector requirements, high level of the cooperatives requirement in relation to/ compared to cooperative members, competitiveness among cooperative members, moderator power of the network, central marketing and internationalization of cooperatives. The restrictive factors highlighted were: equivocal partnerships, impossibility to open the capital, lack of formal mechanisms for the provision of joint accounts, competition among cooperatives, different organizational cultures, power games, resistance to change, lack of market vision, resistance to innovation and absence of projects of internationalization. The framework shows that governance/management of the network is the main driving factor of the inter-cooperation. From the governance/management, the image of reputation/behavior of the involved cooperatives and of the network itself is formed. The reputation/behavior impacts on the governance/management, because this causal relationship is relevant to the formation of alliances based on responsibilities and reciprocal benefits. This relationship between governance/management and reputation/behavior influences in the development of cooperation strategies that, if implemented in a successful way, reinforces the image generated by the reputation/behavior of the network in its environment of operation. The strategies of cooperation aim at promoting the evolution of cooperation and, when/where appropriate, the internationalization of cooperatives. The results of the development/performance of cooperation and internationalization can promote competitive advantages to ensure the survival and growth of cooperatives and the network itself. The main contributions of the thesis, in addition to the framework proposed, are: the identification of the operation factors of agri-food cooperatives that can be propelled/stimulated or restrictive/limited to inter-cooperation, management practices to encourage the latter (inter-cooperation), an analysis of the relation between the number of cooperatives and the type of structure more suitable to the network configuration and the correlation of the framework proposed in the Curve of Wealth, in order to suggest innovations in cooperatives and in the networks. As main suggestion for future study, statistical validation of the proposed framework was indicated.
Keywords: Intercooperação; Cooperação; Cooperativas; Redes horizontais de cooperativas; Inter-cooperation; Cooperation; Cooperatives; Horizontal network of cooperatives; ACCNPQ::Ciências Sociais Aplicadas::Administração